The effectiveness of a proposed program based on communicative theory in teaching Arabic to develop digital intelligence skills for primary school students in Bisha Governorate - Abdelkader, Mahmoud Helal; Matary, Edrees Ali (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the effectiveness of a proposed program based on communicative theory in the Arabic language in developing digital intelligence skills among sixth grade students in Bisha Governorate. The descriptive analytical and semi-experimental approaches were used. A list of digital intelligence skills was prepared, and a digital intelligence test was prepared. And the application was done before and after on a sample of (30) students in the sixth primary, and the results resulted in the following: defining a list of digital intelligence skills amounting to (27) skills, preparing a proposed program based on communication theory to teach the Arabic language, and it was found that there are differences between the two measurements The pre and post scores in the average scores of the digital intelligence test, where the tribal total average was (46.8 out of 100), while the post total average was (86.53), and the differences were statistically significant at the level (0.01) in favor of the post application. The digital intelligence of the sixth primary students, which reached (4.19) according to the ETA square. In the light of these results, the research recommended paying attention to the development of digital intelligence among learners. He also suggested complementary studies on the subject.